2012
DOI: 10.1016/j.eswa.2012.01.088
|View full text |Cite
|
Sign up to set email alerts
|

A probabilistic integrated object recognition and tracking framework

Abstract: Abstract. This paper describes a probabilistic integrated object recognition and tracking framework called PIORT, together with two specific methods derived from it, which are evaluated experimentally in several test video sequences. The first step in the proposed framework is a static recognition module that provides class probabilities for each pixel of the image from a set of local features. These probabilities are updated dynamically and supplied to a tracking decision module capable of handling full and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Besides, this project is part of a larger project in which social robots guide people through urban areas (Garrell & Sanfeliu, 2012) and they have tracking abilities (Serratosa, Alquézar, & Amézquita, 2012). Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, this project is part of a larger project in which social robots guide people through urban areas (Garrell & Sanfeliu, 2012) and they have tracking abilities (Serratosa, Alquézar, & Amézquita, 2012). Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Suresh et al presented an online learning neural tracker with radial basis function network, and the learning algorithm updates the parameters of the nearest neuron to reduce the computational complexity [30]. Serratosa et al exploited a probabilistic integrated object recognition and tracking framework with respectively Bayesian method and a multilayer perceptron, and their test results showed that the perceptron method outperforms the Bayesian [31]. A method for tracking sea surface targets in video using WiSARD weightless NN is presented in [32].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to still images, video sequences provide more information about how objects and scenarios change over time. Over the past years, many interesting applications of traffic monitoring and vehicle tracking using roadside cameras have been proposed and shown to be useful in many situations [1][2][3]. Vehicle tracking systems are presented in order to solve many traffic problems like vehicle routing [4] and accidents detection [5] to name a few.…”
Section: Introductionmentioning
confidence: 99%